A variety of soliton solutions for the fractional Wazwaz-Benjamin-Bona-Mahony equations - Seadawy, Aly R.; Ali, Khalid K.; Nuruddeen, R.I. (Results in physics, 2019)
In the present paper, the new three-dimensional modified Benjamin-Bona-Mahony equations recently introduced are analyzed with the introduction of the spatial and temporal fractional order derivatives using conformable fractional derivative. Various solutions including hyperbolic and periodic function solutions are constructed using simple ansatzs with the aid of the Wolfram Mathematica software. Some graphical representations of the solutions are depicted.